Differential responses of soil microorganisms to precipitation changes in austral semiarid grasslands - Toledo, Santiago; Gargaglione, Veronica Beatriz; Yahdjian, Laura; Peri, Pablo Luis (Elsevier, 2023)
Global climate models predict that precipitation regimes will change, generating great impacts on various ecosystem processes and functions. Therefore, it is important to know how drought and precipitation increases would affect the soil microorganims and plants. We established a precipitation manipulation experiment, with treatments ranging from 54% reduction (drought) to 54% increases (irrigation) in a semiarid ecosystem, and measured microbial carbon (MBC) and nitrogen (MBN), soil basal respiration (SBR), microbial metabolic coefficients (qCO2), and estimated the sequestration and fluxes of CO2 by soil microorganisms. While simulated drought did not modify the microbial community attributes, the microbial biomass increased with greater precipitation, which in the long term could lead to greater carbon (C) sequestration by the microbial pathway and a decline in potential CO2 emissions into the atmosphere. This study shows that microorganisms of the semiarid soil are able to withstand drought and are possibly able to adopt resistance mechanisms under dry conditions. However, drought or increased precipitation did not affect SBR. The results showed that plants’ and soil microorganisms’ responses to precipitation change were asymmetric and different. The study quantifies the contributions of microorganisms to sequestered C by soil microbial biomass (≈35 g MBC m− 2) and CO2 fluxes to the atmosphere (removed in MBC ≈127 g CO2 m− 2 and emission by SBR ≈876 g CO2 m− 2 yr− 1) in semiarid ecosystems. This study not only increases our understanding of the adaptation of soil microorganisms to precipitation changes but also provides new insight into the contributions of the microorganisms when modeling and projecting implications for C cycling.